2019
DOI: 10.1016/j.mimet.2019.02.020
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF MS based procedure to detect KPC-2 directly from positive blood culture bottles and colonies

Abstract: In this study, we identified specific carbapenemase-producing isolates applying an easy and rapid protocol for the detection of mature KPC-2 β-lactamase by MALDI-TOF MS from colony and positive blood culture bottles. In addition, we evaluated the correlation of the ~11,109 Da signal as a biomarker associated with KPC-2 production. A collection of 126 well-characterized clinical isolates were evaluated (including 60 KPC-2-producing strains).Presence of KPC-2 was assessed by MALDI-TOF MS on protein extracts. Sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…It is a question for future analyses to document the differences found by mass spectrometry between KPC producers and non-productive strains of K. pneumoniae in detail. However, Figueroa-Espinosa et al [ 71 ] observed the predicted enzyme KPC-2 β-lactamase (28,544 m/z ) in the mass spectrum of KPC-2 production bacterial strains of the family Enterobacteriaceae , in particular K. pneumoniae , E. cloacae , E. coli , Serratia marcescens, and Citrobacter braakii . Additionally, they were able to detect KPC-2 β-lactamase in P. aeruginosa KPC-2.…”
Section: Resultsmentioning
confidence: 99%
“…It is a question for future analyses to document the differences found by mass spectrometry between KPC producers and non-productive strains of K. pneumoniae in detail. However, Figueroa-Espinosa et al [ 71 ] observed the predicted enzyme KPC-2 β-lactamase (28,544 m/z ) in the mass spectrum of KPC-2 production bacterial strains of the family Enterobacteriaceae , in particular K. pneumoniae , E. cloacae , E. coli , Serratia marcescens, and Citrobacter braakii . Additionally, they were able to detect KPC-2 β-lactamase in P. aeruginosa KPC-2.…”
Section: Resultsmentioning
confidence: 99%
“…There are multiple phenotypic and molecular genotypic tests ( Tamma and Simner, 2018 ) in addition to those listed above that can be used to optimize therapeutic regimens. This includes the use of matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry to identify microorganisms directly in positive blood culture bottles ( Patel, 2015 ) and to identify proteins associated with antimicrobial resistance mechanisms, including carbapenemases, such as KPC-2, in a rapid and cost effective manner ( Gaibani et al., 2016 ; Vrioni et al., 2018 ; Figueroa-Espinosa et al., 2019 ). Earlier differentiation between CPO and non-CPO enhances the ability of antimicrobial stewardship programs to move from empiric to directed antimicrobial therapy to treat infections.…”
Section: Discussionmentioning
confidence: 99%
“…[ 158 , 159 ]. The detection of mass spectrometry peaks of some β-lactamases such as TEM-1 [ 160 ] and KPC-2 [ 161 , 162 ] was shown to distinguish reliably between resistant and susceptible isolates. Cordavana and colleagues designed an algorithm integrated into the MALDI Biotyper System (Bruker DALTONICS, Bremen, Germany) that enables the automated detection of KPC harboring Klebsiella pneumoniae from cultured colonies as well as directly from positive blood cultures during the routine identification process (sensitivity 85.1%; specificity 100%) [ 163 ].…”
Section: Detection and Characterization Of Mdr Enterobacteralesmentioning
confidence: 99%